Standardizing Shirolepa: Bridging Classical Knowledge and Clinical Application (AYUSHDHARA, 2025)
Shirolepa, a time-honored Ayurvedic therapeutic modality, involves the application of medicated Ayurvedic drugs paste on the scalp. It is indicated for various disorders including Shiroroga (head disorders), Manasika rogas (psychological disorders), and skin conditions. Despite its clinical relevance, the absence of standardized protocols has resulted in varied practices, compromising therapeutic consistency and reproducibility. Objective: To review classical references of Shirolepa and develop a standardized clinical protocol that aligns traditional knowledge with contemporary therapeutic needs. Materials and Methods: An extensive literary review was conducted across classical Ayurvedic texts including Charaka Samhita, Sushruta Samhita, Ashtanga Hridaya, Laghutrayi, Yogaratnakara and Gada nigraha. Current clinical applications were assessed through practitioner surveys and review of published clinical studies. Comparative analysis was done to identify variations and common practices in indications, formulations, and application methods. Results: The study identified significant heterogeneity in current clinical practices. Commonly used formulations, indications, application techniques, and retention times were compiled. A standardized protocol for Shirolepa was proposed based on classical references and validated clinical practices. Key components included criteria for patient selection, procedural steps, formulation types, duration, and post-procedure care. Conclusion: Standardization of Shirolepa is imperative for ensuring therapeutic efficacy, safety, and wider clinical applicability. This work provides a framework that integrates classical Ayurvedic principles with practical clinical implementation, paving the way for consistent practice and future research validation.